∫ − 2 2 ∫ − ( 4 − x 2 ) / 2 ( 4 − x 2 ) / 2 ∫ x 2 + 3 y 2 8 − x 2 − y 2 d z d y d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The integral is equal to I = ∬ x 2 + 2 y 2 ≤ 4 ( 8 − 2 x 2 − 4 y 2 ) d x d y = 2 ∬ x 2 + 2 y 2 ≤ 4 ( 4 − x 2 − 2 y 2 ) d x d y = 2 ∬ X 2 + Y 2 ≤ 4 ( 4 − X 2 − Y 2 ) d X d Y = 2 ∫ 0 2 r d r ∫ 0 2 π ( 4 − r 2 ) d θ = 2 π 2 ∫ 0 2 ( 4 r − r 3 ) d r = 2 π 2 [ 2 r 2 − 4 1 r 4 ] 0 2 = 8 π 2 making the answer 3 5 . 5 4 3 0 6 3 5 0 5 . Here we have first performed the integration with respect to z , recognised what is left as the integral over a region in R 2 , introduced a change of variables X = x , Y = y 2 to convert the region of integration to a circle, and then introduced polar coordinates r , θ to complete the integral.
Problem Loading...
Note Loading...
Set Loading...
I = ∫ − 2 2 ∫ − 2 4 − x 2 2 4 − x 2 ∫ x 2 + 3 y 2 8 − x 2 − y 2 d z d y d x = ∫ − 2 2 ∫ − 2 4 − x 2 2 4 − x 2 z ∣ ∣ ∣ ∣ x 2 + 3 y 2 8 − x 2 − y 2 d y d x = ∫ − 2 2 ∫ − 2 4 − x 2 2 4 − x 2 8 − 2 x 2 − 4 y 2 d y d x = ∫ − 2 2 ( 8 − 2 x 2 ) y − 3 4 y 3 ∣ ∣ ∣ ∣ − 2 4 − x 2 2 4 − x 2 d x = ∫ − 2 2 ( 8 − 2 x 2 ) ⋅ 2 ( 2 4 − x 2 ) 2 1 − 3 4 ⋅ 2 ( 2 4 − x 2 ) 2 3 d x = ∫ − 2 2 8 ( 2 4 − x 2 ) 2 3 − 3 8 ( 2 4 − x 2 ) 2 3 d x = ∫ − 2 2 3 1 6 ( 2 4 − x 2 ) 2 3 d x = ∫ − 2 2 3 2 6 4 ( 1 − 4 x 2 ) 2 3 d x = 3 2 1 2 8 ∫ − 2 π 2 π cos 4 θ d θ = 3 2 2 5 6 ∫ 0 2 π sin 0 θ cos 4 θ d θ = 3 2 1 2 8 B ( 2 1 , 2 5 ) = 3 2 1 2 8 ⋅ Γ ( 3 ) Γ ( 2 1 ) Γ ( 2 5 ) = 3 2 1 2 8 ⋅ 2 ! π ⋅ 2 3 ⋅ 2 1 Γ ( 2 1 ) = 2 1 6 π ≈ 3 5 . 5 4 3 Let sin θ = 2 x , d x = 2 cos θ d θ The integral is even. B ( m , n ) is the beta function. Γ ( n ) is the gamma function.
Reference: